Integrating Listening and Speaking Skills to Promote Students’ English Speech Production - Edi Saputra (Jurnal Ilmiah Guru Madrasah, 2024)
Listening and speaking are two interrelated language skills that play a crucial role in English as a Foreign Language (EFL) learning, particularly in developing students’ oral communication ability. However, these skills are often taught separately in classroom practice, which limits students’ opportunities to engage in authentic communication and hinders speech production. This article aims to examine the importance of integrating listening and speaking skills to promote students’ English speech production. Using a conceptual qualitative approach, this study reviews relevant theories and previous studies related to listening-speaking integration. The discussion focuses on the pedagogical benefits of integrated listening-speaking instruction and explores practical classroom strategies such as listen-and-respond tasks, role-play and simulation, information gap activities, and discussion-based listening. The findings indicate that integrating listening and speaking skills enhances students’ fluency, pronunciation, vocabulary use, confidence, and overall communicative competence. Therefore, this article suggests that listening and speaking integration should be considered a fundamental principle in EFL instruction to support effective speech production and prepare students for authentic communication beyond the classroom